Management of Transnational Higher Education under the Belt and Road Initiative: Growth Scale, Regional Cooperation and Major Category Layout - Su, Jingyao (Transformations In Business & Economics, 2025)
International education exchanges and cooperations are important aspects of the Belt and Road Initiative (BRI). This paper examines the transnational higher education programmes and institutions that China has established in collaboration with the BRI co-construction countries over the past decade. This study presents empirical research on the scale of growth, regional education locations, co-construction countries, as well as characteristics of discipline categories and major categories. The data is analysed using the paired samples Wilcoxon signed-rank test and the chi-square test. The results show a significant increase in the number of international cooperative programmes and institutions. However, the expansion of transnational higher education within the BRI framework demonstrates a trend towards aggregation, with concentration in specific Chinese domestic provinces and cooperation countries, as well as in certain disciplinary fields. At the junior college level, there is a more prominent development in certain major categories, while the trend for undergraduate education is to broaden the scope of international education cooperation. To promote transnational cooperation in higher education, it is important to consider the regional advantages, the urgent needs of both university partners, job market needs, and industry development. This approach represents the future development direction for international education cooperation.